2014
DOI: 10.1245/s10434-014-3741-3
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Quality of Care Data for Colon Cancer Surgery: Comparison of Synoptic and Dictated Operative Reports

Abstract: Synoptic reports were associated with more complete documentation of quality indicators for colon cancer resection compared to dictated reports. Although synoptic reports may improve the documentation of quality of care data, further refinement may help to better document performance of quality measures and improve reporting standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 19 publications
1
52
1
Order By: Relevance
“…In the present study, we evaluated SR using an evidence-based best practices quality checklist that was developed completely independently following the creation of the WebSMR template. The results of this study are consistent with an earlier paper from our group, which showed that SR were associated with more complete documentation of validated quality indicators for colon cancer surgery [5]. In both the present and earlier study, SR had higher scores Journal of Surgical Oncology on the intra-operative care sections, which is important since this section really represents the most central and basic part of an operative report.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, we evaluated SR using an evidence-based best practices quality checklist that was developed completely independently following the creation of the WebSMR template. The results of this study are consistent with an earlier paper from our group, which showed that SR were associated with more complete documentation of validated quality indicators for colon cancer surgery [5]. In both the present and earlier study, SR had higher scores Journal of Surgical Oncology on the intra-operative care sections, which is important since this section really represents the most central and basic part of an operative report.…”
Section: Discussionsupporting
confidence: 91%
“…Operative reports present a medium to record and potentially measure performance of important quality indicators that affect patients undergoing surgical procedures for cancer [5,6]. However, multiple studies have demonstrated that traditional narrative operative reports (NR) often lack important operative details, which make them inadequate for quality assurance purposes [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Review of the literature on synoptic operative reports demonstrates significant advantages over standard dictations for rectal cancer and breast. [3][4][5] It is electronic and web based with dropdown menus; this form of operative report was associated with more complete and reliable documentation. 6 What is unclear from the literature is whether it was associated with actual improved performance, which was the main problem we addressed in our study.…”
Section: Surgical Protocol Violations In Children With Renal Tumors Pmentioning
confidence: 99%
“…suggest another evidence‐based tool to improve surgical quality, the synoptic operative report. Review of the literature on synoptic operative reports demonstrates significant advantages over standard dictations for rectal cancer and breast . It is electronic and web based with dropdown menus; this form of operative report was associated with more complete and reliable documentation .…”
mentioning
confidence: 99%
“…Traditional narrative operative notes have recognized fallibilities for use in cancer surgery . Edhemovic et al.…”
mentioning
confidence: 99%